First Report of Botrytis Mold Caused by Botrytis cinerea on Peonies (Paeonia lactiflora Pall.) - Hyo Jeong Kim; Min Young Park; Kyung-Cheol Ma; Young Cheol Kim (Research in Plant Disease, 2020)
In 2019, symptoms of Botrytis mold on the peony (Paeonia lactiflora Pall.) 'Sarah Bernhardt' were observed during a survey of the commercial greenhouses of Gangjin County, South Korea. The initial symptoms, small brown spots, were observed mainly at the leaf margins. The lesions extended to the interior of leaves forming irregular spots in which abundant conidia developed. Fungal colonies were obtained from surface-sterilized tissue excised from growing edges of the lesions that were transferred to potato dextrose agar. Melanized irregular sclerotia were formed in these colonies after 40 days at 8°C. Molecular phylogeny based on sequences of genes for glyceraldehyde-3-phosphate dehydrogenase, heat-shock protein 60, and RNA polymerase subunit II were highest for the PBC-2 isolate to the type strains of Botrytis cinerea, rather than other Botrytis species associated with peony diseases. Following Koch's postulates, healthy Sarah Bernhardt plants were inoculated with a foliar application of conidial suspensions of the isolate PBC-2. Following incubation under humidity with a 12 hr photoperiod for 7 days, symptoms developed on the leaf margins that were identical to those observed in the greenhouses. This study is the first report of Botrytis blight caused by B. cinerea on peonies grown in commercial greenhouses in South Korea.